2020
DOI: 10.1101/2020.09.10.20191882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial pulmonary superinfections are associated with unfavourable outcomes in critically ill COVID-19 patients

Abstract: Objectives While superinfections are associated with unfavourable disease course, their impact on clinical outcomes in critically ill COVID-19 patients remains largely unknown. We aimed to investigate the burden of superinfections in COVID-19 patients. Methods In this prospective single centre cohort study in an intensive care setting patients aged ≥ 18 years with COVID-19 acute respiratory distress syndrome were assessed for concomitant microbial infections by longitudinal analysis of tracheobronchial secreti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…aeruginosa infection in CF patients is a common finding and about 70% of cases and controls in our study had positive sputum cultures for P. aeruginosa and were treated aggressively with IV antibiotics, as per standard practice. Bacterial superinfection, with P. aeruginosa has been associated with longer duration of ventilation in critically ill COVID-19 patients [14], but this was not the case for our patients, none of whom required mechanical ventilation.…”
Section: Plos Onementioning
confidence: 53%
“…aeruginosa infection in CF patients is a common finding and about 70% of cases and controls in our study had positive sputum cultures for P. aeruginosa and were treated aggressively with IV antibiotics, as per standard practice. Bacterial superinfection, with P. aeruginosa has been associated with longer duration of ventilation in critically ill COVID-19 patients [14], but this was not the case for our patients, none of whom required mechanical ventilation.…”
Section: Plos Onementioning
confidence: 53%
“…There are studies describing the involvement of dental caries [15][16][17][18]; in contrast, there are studies not related to dental caries [19,20]. It may be the feature of CA that discussion in [3][4][5][6][7][8][9][10][11][12] similar to VAP has generated. In these studies, there was no analysis of the infection caused by CA, the application of the antifungal agent was stopped, and there was no plan against re-infection; moreover, studies have been reported regarding the use of antifungal agents for infection in root canal (Pseudomonas [9] is treated as an important pathogenic bacteria of apical periodontitis), but there is a lack of studies on the propriety of application of the antifungal agent after disinfection, and the technique and extent of maintenance to achieve permanent prevention of transmission and full disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies describing the involvement of dental caries [1 5-18]; in contrast, there are studies not related to dental caries [1 9, 20]. It may be the feature of CA that discussion in [3][4][5][6][7][8][9][10][11][12] similar to VAP has generated. In these studies, there was no analysis of the infection caused by CA, the application of the antifungal agent was stopped, and there was no plan against re-infection; moreover, studies have been reported regarding the use of antifungal agents for infection in root canal (Pseudomonas [9] is treated as an important pathogenic bacteria of apical periodontitis), but there is a lack of studies on the propriety of application of the antifungal agent after disinfection, and the technique and extent of maintenance to achi eve permanent prevention of transmission and full disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CA colonization on airway is associated with pneumonia, malignant tumors, failure of organ transplantation, ocular opacities, digestive disorders, and respirator y disorders [3][4][5][6][7][8][9][10][11]. Moreover, a recent study [12] suggested an adverse influence of COVID-19-associated pneumonia with CA, on the oral cavity, pharynx, heart, liver, spleen, central nervous system, urinary organs, eye, skin, vagina, and the endocrine system, any of which can be the cause of the infection [1,2]. This leads to a synergistic biofilm formation which causes virulence [13].…”
Section: Introductionmentioning
confidence: 99%